2014
DOI: 10.1002/2013jd020337
|View full text |Cite
|
Sign up to set email alerts
|

Satellite observations of CO2 from a highly elliptical orbit for studies of the Arctic and boreal carbon cycle

Abstract: Here we report on an observing system simulation experiment (OSSE) to compare the efficacy of near-infrared satellite observations of CO 2 from a highly elliptical orbit (HEO) and a low Earth orbit (LEO), for constraining Arctic and boreal CO 2 sources and sinks. The carbon cycle at these latitudes (~50-90°N) is primarily driven by the boreal forests, but increasing anthropogenic activity and the effects of climate change such as thawing of permafrost throughout this region could also have an important role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 99 publications
(103 reference statements)
0
26
0
Order By: Relevance
“…However, GOSAT, Orbiting Carbon Observatory-2, and other satellites that rely on passive near-IR techniques for measuring total column CO 2 , including missions using highly elliptical orbits to obtain dense high-latitude sampling (22), require sunlight reflected from the Earth's surface and thus, return poor sample yield during the long, dark cold season. Even for cold season measurements, passive IR techniques are challenged by signals in large air masses because of high solar zenith angles.…”
Section: Resultsmentioning
confidence: 99%
“…However, GOSAT, Orbiting Carbon Observatory-2, and other satellites that rely on passive near-IR techniques for measuring total column CO 2 , including missions using highly elliptical orbits to obtain dense high-latitude sampling (22), require sunlight reflected from the Earth's surface and thus, return poor sample yield during the long, dark cold season. Even for cold season measurements, passive IR techniques are challenged by signals in large air masses because of high solar zenith angles.…”
Section: Resultsmentioning
confidence: 99%
“…Imaging from geostationary orbit (GEO) imagers like NASA's GeoCarb mission (O'Brien et al, 2016;Polonsky et al, 2014) could offer sampling during different periods 555 within a day to constrain the diurnal profile of emissions. Highly elliptical orbit (HEO) imagers could also provide observations at northern high latitudes with a similar high frequency as GEO (Nassar et al, 2014). However, even though multiple space-https://doi.org/10.5194/gmd-2019-326 Preprint.…”
Section: Figurementioning
confidence: 99%
“…Mission enhancements were also considered to measure CO 2 , CH 4 , CO, O 3 , NO 2 , SO 2 , aerosols, temperature and water vapor (LaChance et al, ; McConnell et al, ). An OSSE demonstrated that the CO 2 observations from HEO would provide much improved constraints on ABZ terrestrial biospheric CO 2 fluxes relative to GOSAT (Nassar et al, ), especially during the summer months when the expected CO 2 fluxes (due to boreal forest growth or disturbances or permafrost thaw) and their uncertainties would both be largest. Other advantages, including the diurnal coverage available from HEO and imaging capability, were not assessed in the OSSE, but would contribute further information needed to reduce uncertainty in ABZ CO 2 and CH 4 fluxes.…”
Section: Highly Elliptical Orbits For Remote Sensing Of the Abz (Ray mentioning
confidence: 99%